The Effect of a Mineralized Bone Graft on the Surface Microhardness of Mineral Trioxide Aggregate and Biodentine - Rahimi, Saeed; Shahi, Shahriar; Torabi, Zahra; Rezaie, Yashar; Ghasemi, Negin; Abolhasani, Somayeh (Iranian Endodontic Journal, 2019)
Introduction: This study was designed to determine the effect of Osteon II mineralized bone powder on the surface microhardness of two retrofilling materials: Mineral trioxide aggregate (MTA) and Biodentine (BD). Methods and Materials: Each retrograde material was mixed and carried into 30 sterile custom-made plastic cylinders. Half of the samples in each group were exposed to Osteon II. All cylinders were submerged in simulated tissue fluid and incubated at 37°C and 100% relative humidity for 7 days. Surface microhardness values of each study group was attained using Vicker’s microhardness test. The data were analyzed statistically using two-way ANOVA and independent t test at a significance level of 0.05. Results: In all the setting conditions, BD had significantly greater surface microhardness than MTA (P<0.001). Surface microhardness of both materials was significantly reduced in the presence of osteon II (P=0.006 for BD and P<0.001 for MTA). Conclusion: Mineralized bone graft materials negatively affect surface microhardness of both MTA and BD. In presence of osteon II, BD had the highest surface microhardness. Keywords: Biodentine; Bone Graft Materials; Mineral Trioxide Aggregate; Vickers Microhardness Test